War and conflict (translation. a transdisciplinary journal, 2022)
The urgent, political need for skilled translators became abundantly clear in the tragic wake of 9/11, as institutions charged with protecting national security scrambled to find linguistically proficient specialists to decode intercepts and documents.Translation and global diplomacy seemed never to have been so mutually implicated.